2005
DOI: 10.1093/toxsci/kfi102
|View full text |Cite
|
Sign up to set email alerts
|

Metabonomics in Toxicology: A Review

Abstract: Metabonomics and its many pseudonyms (metabolomics, metabolic profiling, etc.) have exploded onto the scientific scene in the past 2 to 3 years. Nowhere has the impact been more profound than within the toxicology community. Within this community there exists a great deal of uncertainty about whether metabonomics is something to count on or just the most recent technological flash in the pan. Much of the uncertainty is due to unfamiliarity with analytical and chemometric facets of the technology and the attend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
341
0
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 486 publications
(349 citation statements)
references
References 121 publications
2
341
0
6
Order By: Relevance
“…In humans, metabolomics has been used mainly in studies focusing on diagnosis of disease [9,11,15,25,32,39,40,56,58], mode of drug/toxin action [4,31,36,42,47], and characterisation of novel foods [10,48]. However, several recent commentary articles have suggested that metabolomics will have great value for nutritional studies [12, 16-20, 38, 62, 65] and thus it is timely to exploit this technology platform to assess dietary exposure.…”
Section: Metabolomics Approaches Applied To Measurement Of Dietary Exmentioning
confidence: 99%
“…In humans, metabolomics has been used mainly in studies focusing on diagnosis of disease [9,11,15,25,32,39,40,56,58], mode of drug/toxin action [4,31,36,42,47], and characterisation of novel foods [10,48]. However, several recent commentary articles have suggested that metabolomics will have great value for nutritional studies [12, 16-20, 38, 62, 65] and thus it is timely to exploit this technology platform to assess dietary exposure.…”
Section: Metabolomics Approaches Applied To Measurement Of Dietary Exmentioning
confidence: 99%
“…Although it is early days, it is gratifying that the kinds of molecule being observed do correlate with what is to be expected consequently, e.g. upon nephrotoxicity or hepatotoxicity [93].…”
Section: Toxicity Analysesmentioning
confidence: 99%
“…Until recently, most of the work in metabolomics was focused primarily on clinical or pharmaceutical applications such as drug discovery, drug assessment, clinical toxicology, clinical chemistry, cancer research, or food science and nutrition. [21][22][23][24] Within the past few years, metabolomics has also emerged as a field of increasing interest in the context of doping control. If metabolomics only became possible as a result of recent technological breakthroughs in small molecule separation and identification, the complete workflow includes several steps with as many associated skills from the very initial design of the animal experiment to the practical implementation of the tool through sample preparation, sample fingerprinting, data treatment, and analysis and biomarkers structural elucidation.…”
Section: Introductionmentioning
confidence: 99%